Increase of theta frequency is associated with reduction in regional cerebral blood flow only in subjects with mild cognitive impairment with higher upper alpha/low alpha EEG frequency power ratio - Moretti, Davide v.; prestia, annapaola; Binetti, giuliano; Zanetti, orazio; Frisoni, giovanni b. (Frontiers in Behavioral Neuroscience, 2013)
Background: several biomarkers have been proposed for detecting Alzheimer's disease (AD) in its earliest stages, that is, in the predementia stage. In an attempt to find noninvasive biomarkers, researchers have investigated the feasibility of neuroimaging tools, such as MRI, SPECT as well as neurophysiological measurements using EEG. Moreover, the increase of EEG alpha3/alpha2 frequency power ratio has been associated with AD-converters subjects with mild cognitive impairment (MCI). Objective: to study the association of alpha3/alpha2 frequency power ratio with regional cerebral blood flow (rCBF) changes in subjects with MCI . Methods: 27 adult subjects with MCI underwent EEG recording and perfusion single-photon emission computed tomography (SPECT) evaluation. The alpha3/alpha2 frequency power ratio was computed for each subject. Two groups were obtained according to the median values of alpha3/alpha2, at a cut-off of 1.17. Correlation between brain perfusion and EEG markers were detected. Results: subjects with higher alpha3/alpha2 frequency power ratio showed a constant trend to a lower perfusion than low alpha3/alpha2 group. The two groups were significantly different as about the hippocampal volume and correlation with the theta frequency activity. Conclusion: there is a complex interplay between cerebral blood flow, theta frequency activity and hippocampal volume in MCI patients with prodromal Alzheimer's disease, characterized by higher EEG alpha3 /alpha2 frequency power ratio.